2019
DOI: 10.1016/j.jbusres.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

HR outsourcing: The impact on HR's strategic role and remaining in-house HR function

Abstract: Past research on HR outsourcing (HRO) has offered conflicting views about its impact on HR's strategic position. This study highlights the processes by which decisions to outsource HR are made, followed by the processes implemented post such decisions and their effect on the HR function. Using a case study approach and semi-structured interviews (N=35) within a German subsidiary of a US MNC, we provide a framework of HR processes seeking to achieve standardization in terms of harmonization of HR activities acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
(66 reference statements)
1
18
0
1
Order By: Relevance
“…For BM3 Outstaffing, the most connected are staffing agencies and professionals themselves. Removing these factors would destroy the outsourcing business model (Patel et al, 2019 ). BM2 business model “custom calculations” is the most related to customers who systematically use calculation results and software vendors (Iqbal et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For BM3 Outstaffing, the most connected are staffing agencies and professionals themselves. Removing these factors would destroy the outsourcing business model (Patel et al, 2019 ). BM2 business model “custom calculations” is the most related to customers who systematically use calculation results and software vendors (Iqbal et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, researchers found a framework for coordinating HR activities within the organization's branches through HR processes. Also, they found that outsourcing HR practices within the organization has reduced HR flexibility, reduced HR processing time, decreased satisfaction and increased work of HR managers (Patel et al, 2017). In another analysis, the results indicate that companies that have customer-oriented approaches have the potential to outsource HR informal activities more than companies with analytical and defensive strategies (Mishra et al, 2018).…”
Section: K 499mentioning
confidence: 99%
“…The most frequently outsourced activities are those that are not part of the core competencies, i.e. not related to the competitive advantage (Patel et al, 2019).…”
Section: Outsourcing and Service Qualitymentioning
confidence: 99%